Factors associated with fatalism in the face of COVID-19 in 20 Peruvian cities in March 2020 - Christian R. Mejia; Alan Quispe-Sancho; J. Franco Rodriguez - Alarcon; Laura -; Vania L. Ponce-López; Elizabeth S. Varela-Villanueva; Rahi K. Marticorena-Flores; Scherlli E. Chamorro-Espinoza; Maryori S. Avalos-Reyes; Jean J. Vera-Gonzales (Universidad de Ciencias Médicas de La Habana, 2020)
Introduction: The COVID-19 pandemic has generated diverse reactions, but these have not yet been measured in the Latin American population. Objective: To determine the factors associated with the perception of fatalism in the face of COVID-19 infection in inhabitants of 20 cities in Peru. Material and Methods: A cross-sectional, multicenter study with a sample size of 2 466 people from 20 cities of Peru that measured fatalism during the COVID-19 pandemic was conducted through a validated survey (Cronbach´s alpha: 0,78) consisting of 7 items. Statistical analysis was conducted in terms of each city, and p < 0,05 was considered significant. Results: Of the 2 466 respondents, 36 % were depressed, 26 % thought that they might die, 17 % say that this was evidence of the end of the world, and 9 % could make a fatal decision. Women were more likely to engage in three of the fatalistic behaviors (becoming infected, p = 0,020; infecting others, p = 0,004, and becoming depressed, p = 0,020). At an older age there were 5 perceptions (infecting others, p = 0,007; becoming complicated, p < 0,001; becoming depressed, p < 0,001, thinking they would die, p < 0,001; or committing suicide, p = 0,014). Those at risk of complications of COVID-19 had 4 perceptions (infecting others, p = 0,024; becoming complicated, p = 0,002; thinking they would die, p < 0,001; and thinking that this is a sign of the end of the world, p = 0,039). Respondents who were agnostic exhibited a lower frequency in 5 perceptions, while atheist respondents showed a lower frequency in 2 perceptions. Conclusion: Many fatalistic ideas are found among the population in the face of the coronavirus pandemic.